L’ITALIANO DI SICILIANI A LIEGI - ZAMBITO, Giovanni (Studia Universitatis Babeș-Bolyai Philologia, 2018)
The Italian of Sicilians in Liège. This article is a part of field research on the Italian spoken by Italian immigrants in Liège, the biggest city of Wollonia and the capital of the Belgian province of Liège. The main purpose of the work is to outline the research done on the linguistic situation of three generations of Italian immigrants living in Liège. It is clear that the Italian language is variously used especially if the speakers are individuals of different generations, with two typical phenomena which characterize the migration’s language: lexical transfer and code switching. We have identified three varieties of Italian Language: an Italian influenced by dialect, particularly among people of first generation, an Italian more or less new-standard, equivalent to lower-middle regional Italian, typical of second generation with closer ties with Italy and, finally, an Italian with multilingual sentences and expressions, typical of new generations with closer ties with Belgium. In the following paper the protagonists are Enza and Franco, a Sicilian pair, belonging to second generation. Rezumat. Italiana sicilienilor din Liège. Acest articol face parte dintr-o cercetare de teren consacrată italienei vorbite de imigranții italieni în Liège, cel mai mare oraș din Valonia și capitală a provinciei belgiene Liège. Obiectivul principal al lucrării este de a oferi o privire generală asupra situației și comportamentului lingvistic al celor trei generații de imigranți italieni cu reședința în Liège. Este clar că limba italiană este folosită în mod divers, în special dacă vorbitorii sunt persoane de diferite generații, marcate de două fenomene tipice pentru limbajul migrației: transferul lexical și schimbarea de cod. Am identificat trei varietăți de limbă italiană: una influențată de dialect, în special în rândul celor din prima generație, alta mai mult sau mai puțin standardizată, echivalentă cu italiana de nivel inferior-mijlociu, tipică pentru a doua generație, cu legături mai strânse cu Italia și, în sfârșit, o varietate de italiană cu propoziții și expresii multilingve, tipică generațiilor noi cu legături mai strânse cu Belgia. În cele ce urmează, protagoniștii sunt Enza și Franco, un cuplu sicilian aparținând celei de a doua generații. Cuvinte cheie: italiană, belgiană, lingvistică, imigrație, Sicilia, dialect, franceză, interferențe.